W obronie nadinterpretacji (niekoniecznie prawniczej...) - polemika z Fishem - Przymuszała, Beata (Wydawnictwo Naukowe UAM, 2005)
The formula of "defence of overinterpretation" referred to in the title of this article must be received in the context of S. Fish's conception of paninterpretationism, according to which there is no possibility of verification of readings of a text. Fish assumes that we only compare interpretations and we do not have any access to "the text itself". Arguing with this interpretation, I refer to a legal conception (after all the one used by Fish) of interpretation of laws (confining the analysis to Polish doctrine). In spite of this researcher's claim (everybody "uses" laws for their own goals) the theory of interpretation indicates the necessity of separating the linguistic exegesis (explanation, interpretation) of a law which becomes a point of reference for the system, functional and axiological interpretation. The possibility of departures from the linguistic interpretation requires the existence of specific conditions threatening the system of values and at the same time is a proof of the importance of this type of interpretation. Thus, differentiation of interpretation takes into account the linguistic dimension of a text, allowing to speak about interpretations which "are not in accordance with the law". Transferring these views from the study of the press onto the studies of literature one can see the closeness of this approach to U. Eco's interpretations (the "intentio operis" conception) or - on Polish grounds - K. Bartoszyhski's and H. Markiewicz's views. "The defence of overinterpretation" appears to be a defence of the possibility of differentiating of interpretation and performing its verification.
In the defence of overinterpretation (not necessarily the legal one) - a polemic with Fish